2020
DOI: 10.1016/j.mri.2019.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging (MRI) studies of knee joint under mechanical loading: Review

Abstract: Osteoarthritis (OA) is a very common disease that affects the human knee joint, particularly the articular cartilage and meniscus components which are regularly under compressive mechanical loads. Early-stage OA diagnosis is essential as it allows for timely intervention. The primary noninvasive approaches currently available for OA diagnosis include magnetic resonance imaging (MRI), which provides excellent soft tissue contrast at high spatial resolution. MRI-based knee investigation is usually performed on j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 118 publications
(175 reference statements)
0
34
0
2
Order By: Relevance
“…Conventional radiography of the Kellgren-Lawrence stage division has been considered as a standard for describing the severity of KOA [27] . However, we choose the MRI of Recht grade as a result of it can assess soft tissue preferably and KOA affects the articular cartilage particularly [28,29] .…”
Section: Discussionmentioning
confidence: 99%
“…Conventional radiography of the Kellgren-Lawrence stage division has been considered as a standard for describing the severity of KOA [27] . However, we choose the MRI of Recht grade as a result of it can assess soft tissue preferably and KOA affects the articular cartilage particularly [28,29] .…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging interpretation plays an important role in planning surgical treatment of meniscal pathology as there are significant changes of the meniscal tissue and mechanical characteristics after surgical treatment [6]. Meniscectomy usually lead to some mechanical load transmission changes across the joint and hence degenerative changes will be a sequel of major unplanned meniscectomy [11]. In our case, MRI showed the size and the extent of the meniscal flap and limited partial meniscectomy was planned aiming for best short- and long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CT is much more efficient in the modeling of sharply distinct density variations, for example the interface between bone and soft tissues. The latter approach (MRI), however, is preferable when soft tissues are involved because MRI is highly capable of differentiating the soft tissue types and distinguishing the boundaries of the tissues with similar density [19,20]. Hence, for modeling the damaged bone and the replacing bone scaffolds, CT scans can be favorably used.…”
Section: Anatomical Data Acquisitionmentioning
confidence: 99%
“…Furthermore, the nozzle diameter is very important in bioprinting where inappropriate diameter can induce mechanical damage to the cell membrane during 3D bioprinting process. Chang et al [273] studied the effects of nozzle diameter (150, 250, 400 μm) and dispensing pressure (5,10,20, and 40 psi) of a 3D bioprinting technique on HepG2 liver cells recovery and proliferation. The results of their study showed that the mechanical damage to the cells due to increase in dispensing pressure or decrease in nozzle diameter, caused the cell viability to decrease (53.39% at 40 psi and 23.07% at 150 μm).…”
Section: D Printing Process Optimizationmentioning
confidence: 99%